Death by Carbs: Added Sugars and Refined Carbohydrates Cause Diabetes and Cardiovascular Disease in Asian Indians - Bhardwaj, Bhaskar (Mo Med, 2016)
By the year 2030, India will supplant China as the world’s most populous nation. Rapid urbanization and an increasingly Westernized diet and lifestyle, in a population with genetic predisposition to insulin resistance is fueling a rising epidemic of non-communicable diseases in India. A diet that is high in processed foods, added sugars and other refined carbohydrates is a principle factor driving the growing epidemics of type 2 diabetes (T2D), hypertension (HTN), and cardiovascular (CV) disease (CVD). Immediate postprandial spikes in the blood levels of glucose and triglycerides cause immediate parallel rises in oxidative stress, inflammation, and endothelial dysfunction; eventually leading to T2D, and CVD. Furthermore the Asian Indian population is particularly susceptible to exaggerated rises in postprandial glucose and triglycerides because they are genetically predisposed to metabolic syndrome (MetSyn), insulin resistance, and T2D. A diet restricting the consumption of refined carbohydrates and limiting added sugars to not more than 5 grams/day should be adopted by Asian Indians to reduce risk of T2D, HTN, coronary disease, and stroke.